Association of luteal cell degeneration and progesterone deficiency with lysosomal storage disorder mucolipidosis type IV in Mcoln1−/− mouse model. Issue 4 (18th July 2019) - Wang, Zidao; El Zowalaty, Ahmed E; Li, Yuehuan; Andersen, Christian L; Ye, Xiaoqin
Abstract: Transient receptor potential cation channel, mucolipin subfamily, member 1 (TRPML1) ( MCOLN1 / Mcoln1 ) is a lysosomal counter ion channel. Mutations in MCOLN1 cause mucolipidosis type IV (MLIV), a progressive and severe lysosomal storage disorder with a slow onset. Mcoln1 −/− mice recapitulate typical MLIV phenotypes but roles of TRPML1 in female reproduction are unknown. Despite normal mating activities, Mcoln1 −/− female mice had reduced fertility at 2 months old and quickly became infertile at 5 months old. Progesterone deficiency was detected on 4.5 days post coitum/gestation day 4.5 (D4.5). Immunohistochemistry revealed TRPML1 expression in luteal cells of wild type corpus luteum (CL). Corpus luteum formation was not impaired in 5–6 months old Mcoln1 −/− females indicated by comparable CL numbers in control and Mcoln1 −/− ovaries on both D1.5 and D4.5. In the 5–6 months old Mcoln1 −/− ovaries, histology revealed less defined corpus luteal cord formation, extensive luteal cell vacuolization and degeneration; immunofluorescence revealed disorganized staining of collagen IV, a basal lamina marker for endothelial cells; Nile Red staining detected lipid droplet accumulation, a typical phenotype of MLIV; immunofluorescence of heat shock protein 60 (HSP60, a mitochondrial marker) and in situ hybridization of steroidogenic acute regulatory protein (StAR, for the rate-limiting step of steroidogenesis) showed reduced expression of HSP60 and StAR, indicating impaired mitochondrial functions. Luteal cell degeneration and impaired mitochondrial functions can both contribute to progesterone deficiency in the Mcoln1 −/− mice. This study demonstrates a novel function of TRPML1 in maintaining CL luteal cell integrity and function. Abstract : Summary Sentence Our finding that Mcoln1 −/− female mice have luteal cell degeneration and progesterone deficiency reveals a novel role of TRPML1 in luteal cell survival and function.